Gambaran Kasus Demam Berdarah Dengue (DBD) di Provinsi Jawa Barat Tahun 2016-2020 - Anggi Helena Elizabeth; Ririh Yudhastuti (Universitas Airlangga, 2023)
Background: Dengue Hemorrhagic Fever (DHF) has become a problem in public health globally, including in Indonesia which is the country with the highest cases of dengue in Southeast Asia. West Java province itself is the most populous province in Indonesia, and is the region with the highest number of dengue cases in 2020. Objectives: This study aims to draw dengue cases in West Java Province in 2016-2020. Methods: This research was descriptive research with case series design. The data sources in this study used secondary data, namely total population DBD case data obtained from the West Java Provincial Health Profile in 2016-2020, the climate (temperature, humidity, rainfall, duration of sunshine), and population density obtained from the Central Statistics Agency of West Java Province in 2016-2021. Results: Dengue cases in West Java Province with the highest number occurred in 2016. The majority of the population who suffered was male, with the Bandung City occupying the highest position of dengue cases. The IR value of dengue fever in West Java Province in 2016-2020 had not met the national target, while the CFR value had met the national target. When the temperature, rainfall, and sunshine duration are high dengue cases will be low, except for the humidity. Conclusions: Dengue cases in West Java Province experienced fluctuations from 2016-2020, with the factors that affect the occurrence of dengue fever every year in all districts/cities of West Java Province.